2011
DOI: 10.1134/s0965545x11050154
|View full text |Cite
|
Sign up to set email alerts
|

Crazing of isotactic polypropylene in the medium of supercritical carbon dioxide

Abstract: Uniaxial tensile drawing of films based on semicrystalline isotactic PP in the medium of supercrit ical carbon dioxide at a pressure of 10 MPa and a temperature of 35°C is studied. The tensile drawing of PP is shown to proceed in the homogeneous mode without necking and is accompanied by intense cavitation. The maximum level of porosity is 60 vol %. The porous structure that develops owing to the tensile drawing of the polymer in supercritical CO 2 is provided by formation of a set of crazes that are primarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…This porous structure was quite different from that obtained under CO 2 at 2 MPa and under atmospheric pressure at elevated temperatures. A fibrillar-shaped porous structure was not obtained by stretching crystalline polymers under CO 2 where small voids (in a nanometer scale) were formed in the intercrystalline amorphous region [10,46,47], but this structure was similar to that obtained by a specially designed continuous three-point bending method [48,49,50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This porous structure was quite different from that obtained under CO 2 at 2 MPa and under atmospheric pressure at elevated temperatures. A fibrillar-shaped porous structure was not obtained by stretching crystalline polymers under CO 2 where small voids (in a nanometer scale) were formed in the intercrystalline amorphous region [10,46,47], but this structure was similar to that obtained by a specially designed continuous three-point bending method [48,49,50].…”
Section: Resultsmentioning
confidence: 99%
“…Another is disentanglement crazing, which is caused by chain disentanglement due to accelerated molecular motion. In crystalline polymers, voids are formed in the intercrystalline amorphous region by stretching [46] and the void formation is enhanced by stretching under CO 2 [10,47]. On the other hand, in amorphous polymers, we found that a filament-shaped porous structure with periodic distance was obtained macroscopically throughout the whole specimen in OD-PC by stretching under compressed CO 2 [21].…”
Section: Introductionmentioning
confidence: 99%
“…The size was calculated by the Guinier method described in the work. [ 60 ] The thickness of the lamellae was determined as d = Lsaxs × ρρχ×χ where L saxs was the large period determined from SAXS; ρ and ρ χ were the densities of the polymer (1.145 g cm −3 ) and its crystalline phase (1.2 g cm −3 ), [ 61 ] respectively; and χ was the sample crystallinity according to the DSC data.…”
Section: Methodsmentioning
confidence: 99%
“…18. Supercritical carbon dioxide was used as AAM; 87 it is a good crazing agent, which causes the same structural rearrangements in crystalline polymers (PP, HDPE) as other liquid media (hydrocarbons) usually used for DSC.…”
Section: B Crazing Of Crystalline Polymersmentioning
confidence: 99%
“…Stress ± strain curves for stretching and shrinkage and repeated stretching in air of PP, which was preliminarily stretched in AAM (supercritical CO2) according to the delocalized solvent crazing mechanism by 100% and completely relaxed upon removal of AAM from its porous structure. 87 Stress /MPa Figure 19. Time dependences of stress in hard-elastic PP stretched by 50%.…”
Section: B Crazing Of Crystalline Polymersmentioning
confidence: 99%